Production process of high-purity high-density polyethylene plastic barrel
By introducing branched high-density polyethylene, modified glass fiber and flame retardant materials into high-density polyethylene plastic buckets, and adopting special process flow, the existing plastic buckets are solved inadequate drop resistance and low environmental stress resistance. and the problem of poor flame retardant performance achieve higher service life and safety.
Patent Information
- Application Number
- CN202411780610.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing high-density polyethylene plastic barrels are prone to break during use, have insufficient drop resistance, and have low environmental stress resistance and flame retardant properties, which affect service life and safety.
By introducing branched high-density polyethylene and modified glass fibers, and adding flame retardants, antioxidants and toughening agents, melt extrusion and injection molding are carried out using twin-screw extruders and injection molding machines, combined with nitrogen blow molding and Fibre glass cloth wrapping technology prepares high-purity high-density polyethylene plastic barrels.
It significantly improves the environmental stress resistance, mechanical properties and flame retardant properties of plastic barrels, extends service life, and enhances drop resistance and safety.
Smart Images

Figure CN119427714A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of production of high-purity plastic barrels, in particular to a production process of high-purity high-density polyethylene plastic barrels. Background Art
[0002] Plastic barrels are mostly used for the storage and transportation of various liquids. They have good characteristics for the packaging of special dangerous goods. They are not easy to break, rust-proof, light, oil-resistant, and highly corrosion-resistant. They are mostly used for the packaging of dangerous goods that require heat preservation, moisture-proof, pressure-resistant, and corrosion-resistant. Plastic barrels are mostly made of polyethylene, polypropylene, polyester and other plastics through blow molding, injection molding, vacuum molding, and rotational molding.
[0003] Polyethylene (PE) is a thermoplastic resin obtained by polymerization of ethylene. In industry, it also includes copolymers of ethylene and a small amount of α-olefins. Polyethylene is divided into high-density polyethylene, low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE) according to the polymerization method, molecular weight and chain structure. High-density polyethylene (HDPE), commonly known as low-pressure polyethylene, has higher temperature resistance, oil resistance, steam permeation resistance and environmental stress cracking resistance compared to LDPE and LLDPE. In addition, it has good electrical insulation, impact resistance and cold resistance, and is often used in blow molding, injection molding and other fields.
[0004] HDPE's simple linear molecular chain structure has high density, high strength and high modulus, but its toughness performance is unsatisfactory, especially in packaging applications containing corrosive media such as lubricants and detergents, or when subjected to long-term internal pressure. It is easy to crack and cause product failure. Its low resistance to environmental stress leads to a reduction in the service life of the material.
[0005] Patent 201910991881.0 reports a high-density polyethylene resin composition for floating photovoltaic barrels and a preparation method thereof. By introducing a combination of multiple light stabilizers such as light stabilizer M535 and light stabilizer 944, a polyethylene composite material with good aging resistance is obtained. However, these added ultraviolet absorbers are easy to migrate in the matrix, and the effect is not significant when used in low dosages. Increasing the dosage ratio will cause the environmental stress resistance of the polyethylene material to decrease and reduce its service life.
[0006] High-density polyethylene has a limiting oxygen index of 17.4%, and is a flammable material. HDPE material burns quickly, generates a large amount of heat / smoke, and is easy to melt and drip when burned, posing a great threat to the safety of life and property, limiting the use and development of polyethylene. Patent CN202210103784.5 reports a heat-resistant degradable plastic and a preparation method thereof, which is prepared by mixed extrusion and granulation of modified starch, polylactic acid, protein polyamide, sorbitol, diethylene glycol ether, glycerol monothioacetate, triethylhexanoin, and functional fillers. The degradable plastic has good heat resistance and impact resistance. However, the addition of combustible additives does not take into account the flame retardant grade and safety of use of the material.
[0007] In the production process of existing plastic barrels, whether it is blow molding, injection molding, vacuum forming, or rotational molding, after the plastic barrel is formed, its anti-fall ability only relies on its own structural design and material strength. It is difficult to enhance the anti-fall ability of the plastic barrel through subsequent processes, which makes the plastic barrel easy to break during use. At the same time, it also has the disadvantages of low notch impact strength and tensile strength, insufficient rigidity, easy aging, brittleness, easy deformation, and easy breakage.
[0008] Plastic barrels are used to contain various solvents, including chemical reagents, medical sterile reagents and high-purity solvents used in various industries. These solvents need to be kept in a high-purity state to prevent the presence of impurity particles from seeping out of the composition or additives of the polyethylene plastic barrel and destroying the purity of the contained solvent. Therefore, high-density polyethylene plastic barrels are also required to have high cleanliness and low dissolution of impurity particles to increase the application range of plastic barrels.
[0009] In summary, in order to meet the needs of different application scenarios of plastic barrels, high-density polyethylene plastic barrels need to have high mechanical strength while maintaining excellent temperature resistance and oil resistance, and at the same time have anti-fall performance to increase service life; due to the low limiting oxygen index of high-density polyethylene materials, it is necessary to improve the flame retardant properties of plastic barrels; improve the environmental stress resistance of plastic barrels and reduce environmental damage to plastic barrels; high-purity high-density polyethylene plastic barrels can maintain extremely low impurity particle dissolution and can be used for the storage and transportation of high-purity solvents.
[0010] Therefore, a production process of high-purity high-density polyethylene plastic barrels is proposed. Summary of the invention
[0011] The object of the present invention is to provide a production process of a high-purity high-density polyethylene plastic barrel. The process comprises the following steps: high-density polyethylene and a monomer olefin are polymerized under the action of an initiator to form a branched high-density polyethylene, modified glass fiber, a flame retardant, an antioxidant, and a toughening agent are added, and the modified polyethylene is obtained by melt extrusion through a twin-screw extruder and injection molding by an injection molding machine. The amount of the initiator and the initiation reaction temperature are changed, and the environmental stress cracking time of the obtained modified polyethylene is 1356h, and the environmental stress resistance is significantly improved. The process comprises the following steps: introducing glass fiber and modifying the glass fiber to increase the compatibility of the glass fiber with a high-density polyethylene matrix material, and the obtained modified polyethylene has a tensile strength of 52MPa and a notched impact strength of 10.4KJ / m 2 , with significantly improved mechanical properties; adding benzoxazine flame retardants and organophosphorus flame retardants to synergistically form a carbon flame retardant process, the limited oxygen index of the obtained high-density polyethylene modified polyethylene is 35%, which has significantly improved flame retardant properties; using high-purity high-density polyethylene, branched high-density polyethylene, modified glass fiber, flame retardant, antioxidant, and toughening agent to melt extrude into modified polyethylene, and blow molding under the action of nitrogen flow, the 0d impurity particle dissolution amount of the prepared high-purity high-density polyethylene plastic barrel is 8 / ml; the 30d impurity particle dissolution amount is 15 / ml, showing a significantly reduced impurity particle dissolution amount; glass fiber cloth is used to wrap the barrel surface to form a stable glass fiber anti-fall layer, and in the 1.5m drop test of the obtained high-density polyethylene plastic barrel, both the straight drop and the corner drop show that the barrel body has no cracks or leakage, showing significantly improved drop resistance.
[0012] To achieve the above object, the present invention provides the following technical solutions:
[0013] A production process of a high-purity high-density polyethylene plastic barrel, characterized in that: the plastic barrel comprises high-purity high-density polyethylene, modified polyethylene, and glass fiber cloth;
[0014] The modified polyethylene comprises 80-120 parts of branched high-density polyethylene, 10-25 parts of modified glass fiber, 5-25 parts of flame retardant, 5 parts of compatibilizer, and 2 parts of antioxidant;
[0015] The branched high-density polyethylene is prepared by melt extrusion of 5-25 parts of lauroyl peroxide, high-density polyethylene, and 10-40 parts of monomer olefin;
[0016] The production process of the plastic barrel comprises the following steps:
[0017] In a clean environment, the modified polyethylene is added into a modified polyethylene raw material storage tank and stirred evenly to obtain a first mixture; the high-purity high-density polyethylene is added into a high-purity polyethylene raw material storage tank and stirred evenly to obtain a second mixture; the first mixture and the second mixture are respectively introduced into a first screw extruder and a second screw extruder to completely melt to obtain molten modified polyethylene and molten high-purity high-density polyethylene;
[0018] In a clean environment, the molten modified polyethylene and the molten high-purity high-density polyethylene are added into a mold with the barrel mouth facing downward, and the blow molding machine blows in a flow rate of 20-50m 3 / h of high-purity nitrogen for blow molding, and continuously blow to obtain a plastic barrel; the plastic barrel is passed through the outside of the mold with a flow rate of 5-15m 3 / h of cooling water to cool and solidify to obtain a polyethylene plastic barrel;
[0019] The polyethylene plastic barrel is cleaned and polished to obtain a rough surface plastic barrel; glass fiber cloth is pasted on the rough surface plastic barrel to obtain a fiber-treated plastic barrel; the fiber-treated plastic barrel is placed in a mold for hot pressing and curing, demolding, and cooling at room temperature to obtain a high-purity and high-density polyethylene plastic barrel.
[0020] Preferably, the monomer olefin is selected from one of 1-propylene, 1-butene, 1-pentene and 1-hexene.
[0021] Preferably, the method for preparing branched high-density polyethylene comprises the following steps:
[0022] The lauroyl peroxide, the high-density polyethylene, and the monomer olefin compound are placed in a vacuum drying oven and dried at 60° C. for 2 hours to obtain a dry material; the dry material is added to a high-speed mixer and stirred at 200 r / min for 30 minutes to obtain a mixed material; the mixed material is added to a twin-screw extruder, subjected to a melt reaction process at a temperature range of 160° C.-200° C., a main engine speed of 80 r / min, and reacted for 2 hours to obtain a reactant; the reactant is crushed by a crusher to obtain a branched high-density polyethylene.
[0023] Preferably, the preparation of the modified glass fiber comprises the following steps:
[0024] The glass fiber is added into a muffle furnace, and burned at 350° C. for 10 minutes to remove the paraffin on the surface to obtain the fired glass fiber; the fired glass fiber is added into a 10% HCl solution for immersion for 2 hours, and vacuum dried at 100° C. for 1 hour to obtain the acidic glass fiber; the silane coupling agent is dissolved in a solution of anhydrous ethanol and deionized water mixed in a ratio of 1:1, and the mixture is mixed at 200 rpm to obtain a mixed solution; the acidic glass fiber is added into the mixed solution, taken out by ultrasonic treatment for 2 hours, and dried at 100° C. to obtain the modified glass fiber.
[0025] Preferably, the silane coupling agent is selected from one of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and methacryloxypropyltrimethoxysilane; and the amount of the silane coupling agent is 1-8 parts.
[0026] Preferably, the flame retardant includes flame retardant 1 and flame retardant 2; the flame retardant 1 is selected from one of benzoxazine derivatives, polyvinyl chloride, polyphenylene ether, and phenolic resin; the flame retardant 2 is selected from one of triphenyl phosphate, tricresyl phosphate, phenyl aluminum phosphinate, and dimethyl methylphosphonate; the component ratio of the flame retardant 1 to the flame retardant 2 is 1-4:1-4.
[0027] Preferably, the operating parameters of the twin-screw extruder are: a screw speed of 250 r / min, a feed speed of 40 r / min, the temperatures from the first temperature zone to the eighth temperature zone are: 170°C, 175°C, 185°C, 185°C, 195°C, 200°C, 190°C, 180°C, and the head temperature is 180°C.
[0028] Preferably, the operating parameters of the twin-screw extruder 2 are: a screw speed of 250 r / min, a feed speed of 40 r / min, the temperatures from the first temperature zone to the eighth temperature zone are: 120°C, 130°C, 140°C, 145°C, 150°C, 160°C, 155°C, 150°C, and the head temperature is 150°C.
[0029] Preferably, the working parameters of the injection molding machine are as follows: the temperatures of zones 1 to 3 are 180°C, 185°C, and 200°C respectively, the nozzle temperature is 180°C; the holding time is 10s, the cooling time is 20s, the holding pressure is 120MPa, the injection temperature is 185°C, and the injection pressure is 45% of the maximum pressure.
[0030] Preferably, the temperature of the screw extruder 1 is 160-200°C, and the temperature of the screw extruder 2 is 120-160°C.
[0031] Preferably, the glass fiber cloth is a strip of glass fiber cloth with a width of 12 cm; the glass fiber cloth is spirally wound on the side wall of the plastic barrel, and each circle of the glass fiber cloth overlaps each other with a width of 6 cm; when the glass fiber cloth is pasted to the bottom of the plastic barrel, the glass fiber cloth is cut into strips with a width greater than the diameter of the bottom of the plastic barrel, the center of the glass fiber cloth strip is aligned and pasted with the center of the circle of the bottom of the plastic barrel, and the two ends extend to the side wall of the plastic barrel, and the glass fiber cloth on the bottom of the plastic barrel is pasted in a cross shape until the glass fiber cloth strip completely covers the bottom of the plastic barrel.
[0032] Preferably, the curing temperature of the hot pressing curing is 90-120° C., the curing time is 30-90 min, and the curing pressure is 40-60 MPa.
[0033] Preferably, the compatibilizer is selected from maleic anhydride grafted ethylene-octene copolymer; and the antioxidant is selected from antioxidant 1010.
[0034] A high-purity high-density polyethylene plastic barrel, the high-purity high-density polyethylene plastic barrel comprises the high-purity high-density polyethylene, the modified polyethylene, and the glass fiber cloth; the high-purity high-density polyethylene plastic barrel is prepared by any of the production processes described above; the environmental stress cracking time of the modified polyethylene of the plastic barrel is 1356h; the tensile strength of the modified polyethylene of the plastic barrel is 52MPa, and the notched impact strength is 10.4KJ / m 2 ; The limiting oxygen index of the modified polyethylene of the plastic barrel is 35%; the 0d impurity particle dissolution amount of the high-density polyethylene plastic barrel is 8 pieces / ml; the 30d impurity particle dissolution amount is 15 pieces / ml; in the 1.5m drop test of the high-density polyethylene plastic barrel, there is no cracking or leakage in the barrel body when falling in a straight line or at an angle.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The present invention uses high-density polyethylene, and monomer olefins react with initiators to obtain branched high-density polyethylene, and adds modified glass fiber, flame retardant, antioxidant, toughening agent, and obtains modified polyethylene material by melt extrusion through a twin-screw extruder and injection molding by an injection molding machine; the branching degree of high-density polyethylene is changed by adjusting the type and amount of monomer olefins and controlling the amount of initiator; since the branched chain part cannot be tightly arranged in the lattice during the crystallization process, the branched chain can be relied on to make the entanglement of the connecting molecules tighter, thereby increasing the environmental stress resistance of the material. By changing the initiation reaction temperature, the environmental stress cracking time of the obtained modified polyethylene is 1356h, which has significantly improved environmental stress resistance.
[0037] 2. The present invention introduces glass fiber and modifies the glass fiber to increase the compatibility of the glass fiber and the high-density polyethylene matrix material, thereby improving the bonding ability between the materials. When subjected to external force, the matrix material transfers the force to the glass fiber, while the glass fiber itself has a large tensile strength and a small deformation, thereby improving the mechanical properties of the modified polyethylene. By controlling the type and amount of the silane coupling agent and adjusting the amount of the modified glass fiber, the obtained modified polyethylene has a tensile strength of 52MPa and a notched impact strength of 10.4KJ / m 2 , with significantly improved mechanical properties.
[0038] 3. The present invention increases the limiting oxygen index of high-density polyethylene plastic by adding flame retardants. The organophosphorus flame retardant generates a glassy melt to isolate oxygen during combustion, and forms a carbon layer to isolate combustion. Benzoxazine has good carbonization property, and can cooperate with the organophosphorus flame retardant to participate in the carbonization flame retardant mode to form a dense carbon layer on the surface of the burning object to achieve a better flame retardant effect. By controlling the type and amount of flame retardant, the limiting oxygen index of the obtained modified polyethylene is 35%, which has significantly improved flame retardant properties.
[0039] 4. The present invention uses high-purity high-density polyethylene, branched high-density polyethylene, modified glass fiber, flame retardant, antioxidant, and toughening agent to melt extrude modified polyethylene to form a high-purity high-density polyethylene plastic barrel. At the same time, a high-purity nitrogen flow is used in the blow molding process to avoid particle pollution in the air, control the temperature of the screw extruder, and the flow rates of nitrogen and cooling water. The prepared high-purity high-density polyethylene plastic barrel has an impurity particle dissolution amount of 8 particles / ml at 0d and 15 particles / ml at 30d, showing a significantly reduced impurity particle dissolution amount.
[0040] 5. The present invention uses epoxy resin adhesive to graft glass fiber cloth, and solidifies and bonds with the surface of the plastic barrel. The glass fiber cloth is wrapped around the surface of the plastic barrel by covalent bonding to form a stable glass fiber anti-fall layer. The glass fiber has high strength and good elastic recovery rate. By controlling the curing temperature, curing time and curing pressure, the high-density polyethylene plastic barrel prepared can be subjected to a 1.5m drop test. Both straight-line drop and corner drop show that the barrel body has no cracks or leakage, showing significantly improved drop resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The dissolution amount of impurities of different particle sizes 0d and 30d is changed in Example 46;
[0042] Figure 2 This is the change in the dissolution amount of 0d and 30d particles of impurities with different particle sizes in comparative example 8. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0045] The high-density polyethylene described in the present invention is selected from DMDY1158, which is purchased from Sinopec Qilu Petrochemical Company.
[0046] The KH-550 described in the present invention is 3-aminopropyltriethoxysilane, CAS: 919-30-2.
[0047] The KH-560 described in the present invention is 3-(2,3-epoxypropoxy)propyltrimethoxysilane, CAS: 2530-83-8.
[0048] The KH-570 described in the present invention is methacryloxypropyltrimethoxysilane, CAS: 2530-85-0.
[0049] The KH-792 described in the present invention is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, CAS: 1760-24-3.
[0050] The BOZ described in the present invention is a benzoxazine derivative.
[0051] The TPP described in the present invention is triphenyl phosphate, CAS: 115-86-6, purchased from Anhui Zesheng Technology Co., Ltd.
[0052] The TCP described in the present invention is tricresyl phosphate, CAS: 1330-78-5, purchased from Tianjin Chemical Reagent Factory No. 1.
[0053] The DMMAP described in the present invention is dimethyl methylphosphonate, CAS: 756-79-6.
[0054] The PADP described in the present invention is aluminum phenylphosphinate, CAS: 25070-21-7.
[0055] The PVC described in the present invention is polyvinyl chloride, which is purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0056] The PPO described in the present invention is polyphenylene ether purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0057] The PFR described in the present invention is phenolic resin purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0058] See also Figure 1-2 The present invention provides a production process of high-purity and high-density polyethylene plastic barrels, and the technical solution is as follows:
[0059] Examples 1-13
[0060] Preparation of modified glass fiber:
[0061] 50 parts of glass fiber were added into a muffle furnace, burned at 350° C. for 10 minutes, and the paraffin on the surface was removed to obtain sintered glass fiber; 50 parts of the sintered glass fiber were added into 10 ml of 10% HCl solution for immersion for 2 hours, and vacuum dried at 100° C. for 1 hour to obtain acidic glass fiber; 5 parts of KH-570 were dissolved in a solution of anhydrous ethanol and deionized water mixed in a ratio of 1:1, and mixed at 200 rpm to obtain a mixed solution; 50 parts of the acidic glass fiber were added into the mixed solution, ultrasonicated for 2 hours, taken out, and dried at 100° C. to obtain the modified glass fiber.
[0062] Preparation of branched high-density polyethylene:
[0063] 5-25 parts of lauroyl peroxide, 80 parts of high-density polyethylene, and 10-40 parts of a monomer olefin compound are placed in a vacuum drying oven and dried at 60°C for 2 hours to obtain a dry material; the dry material is added to a high-speed mixer and stirred at 200 r / min for 30 minutes to obtain a mixed material; the mixed material is added to a twin-screw extruder, and the temperature range is 160°C-200°C for melt reaction processing, the main engine speed is 80 r / min, and the reaction is carried out for 2 hours to obtain a reactant; the reactant is crushed by a crusher to obtain a branched high-density polyethylene.
[0064] The branched high-density polyethylene, 20 parts of the modified glass fiber, 15 parts of the flame retardant, 10102 parts of the antioxidant, and 5 parts of maleic anhydride grafted ethylene-octene copolymer are placed in a vacuum drying oven and dried at 60°C for 2 hours to obtain a dried raw material; the dried raw material is added to a high-speed mixer and stirred at 500 r / min for 30 minutes to obtain a mixed material; the mixed material is added to a twin-screw extruder for melt blending and extrusion, cooled, and pelletized to obtain pellets; the pellets are vacuum dried at 85°C for 5 hours and then injection molded by an injection molding machine to obtain modified polyethylene.
[0065] The specific differences between Examples 1-13 are shown in Table 1.
[0066] Comparative Example 1 refers to the preparation method and parameter conditions of Example 1, except that no monomer olefin is added.
[0067] Comparative Example 2 refers to the preparation method and parameter conditions of Example 1, except that no branching treatment is performed.
[0068] Comparative Example 3 refers to Example 1, except that no initiation reaction is performed and branched high-density polyethylene is obtained by direct blending.
[0069] Example 14 Environmental stress resistance test
[0070] The environmental stress resistance of the modified polyethylene samples prepared in Examples 1-13 and Comparative Examples 1-3 was tested using a NYK-06 environmental stress cracking tester according to GB / T 1842-2008. The size of the tested sample was 38×13×2 mm, and the length and depth of the notch were 19 mm and 0.3 mm, respectively.
[0071] Bend the sample with notches into a "U" shape, fix it on the sample holder, and place it in a test tube. Use a 10% aqueous solution of nonylphenol polyoxyethylene ether (TX-10) as a reagent and test it in a 50℃ high-grade constant temperature water bath. Observe and record the number of cracks and damages on the sample; the time when the probability of damage in a certain medium is 50% is the environmental stress cracking time, that is, F 50 , unit is h, the test results are shown in Table 1.
[0072] Table 1 Environmental stress resistance test results of Examples 1-13 and Comparative Examples 1-3
[0073]
[0074] From the results in Table 1, it can be seen that the environmental stress resistance of the sample obtained by not performing branching treatment on high-density polyethylene in Comparative Example 2 is poor. When the material is blow-molded, the cooling shrinkage is uneven and internal stress exists. During use, the stacking load generates external stress, which is easily affected by the environment, resulting in reduced material performance; Compared with Comparative Example 2, the environmental stress resistance of the samples using branched monomers in Comparative Examples 1 and 3 is significantly improved, and the environmental stress resistance of the samples obtained by initiating olefin polymerization with an initiator is better; From the results of Examples 1-4, it can be seen that the environmental stress resistance of samples with different types of monomers is not much different. The introduction of olefin monomers can increase the content of the branched part. Since the branched part cannot be tightly arranged in the lattice during the crystallization process, the branched chain can be relied on to make the entanglement of the connecting molecules tighter, and at the same time, the number of ligature molecules between crystals is increased, thereby enhancing the connection between crystals and improving the environmental stress resistance performance; Compared with the results of Example 1 and Examples 5-7, it can be seen that with the increase of the amount of initiator, the environmental stress cracking time first increases and then decreases. This is because the excessive initiator makes the coupling point in the reaction system The increase in the amount of monomer olefins reduces the length of the branch chain, tends to the development of the structure, is not conducive to the molecular chain running through the grains and spherulites to form tie molecules, and causes slip cracking between the wafers to occur more easily under environmental stress. At the same time, when the torque reaches equilibrium, the branching reaction time is too long, the molecular chain is degraded, the strengthening effect of the connecting molecules between the wafers is weakened, and the environmental stress resistance is weakened; from the results of Examples 1 and 8-10, it can be seen that with the increase in the amount of monomer olefins, the environmental stress cracking time shows a trend of first increasing and then decreasing. The initiator content is limited. Continuing to increase the amount of monomer olefins is not conducive to the distribution of the molecular chain in the crystallization area and reduces the environmental stress resistance; from the results of Examples 1 and 11-13, it can be seen that with the increase in temperature, the environmental stress cracking time first increases and then decreases. Experiments show that increasing the screw temperature can ensure uniform melt plasticization, but too low a melt temperature will increase the molecular orientation during the filling process and increase the residual stress after cooling and shaping; an increase in mold temperature is conducive to the close stacking of grains and reduces or eliminates internal defects, but too high a temperature is prone to insufficient cooling during demolding, and deformation and warping deformation occurs at ambient temperature. From the results in Table 1, it can be seen that by using 1-hexene as the monomer olefin, controlling the amount of initiator and monomer olefin, and maintaining the reaction temperature within 180-190°C, the environmental stress cracking time of the prepared modified polyethylene is 1356h, which has significantly improved environmental stress resistance.
[0075] Examples 15-27
[0076] Preparation of modified glass fiber:
[0077] 50 parts of glass fiber are added into a muffle furnace, and burned at 350° C. for 10 minutes to remove the paraffin on the surface to obtain the fired glass fiber; the fired glass fiber is added into 10 ml of 10% HCl solution for immersion for 2 hours, and vacuum dried at 100° C. for 1 hour to obtain the acidified glass fiber; the silane coupling agent is dissolved in a solution of anhydrous ethanol and deionized water mixed in a ratio of 1:1, and mixed at 200 rpm to obtain a mixed solution; the alkaline glass fiber is added into the mixed solution, taken out by ultrasonic treatment for 2 hours, and dried at 100° C. to obtain the modified glass fiber.
[0078] The preparation method of the modified polyethylene refers to the preparation method parameter conditions of Example 1.
[0079] Examples 16-27 refer to the preparation method and parameter conditions of Example 15, and the differences are shown in Table 2.
[0080] Table 2 Relationship between the dosage of components in Examples 15-27
[0081]
[0082]
[0083] Comparative Example 4 refers to the preparation method and parameter conditions of Example 15, except that no silane coupling agent is added to modify the glass fiber.
[0084] Comparative Example 5 refers to the preparation method and parameter conditions of Example 15, except that no modified glass fiber is added.
[0085] Example 29 Mechanical Properties Test
[0086] Tensile strength test: The modified polyethylene samples prepared in Examples 15-27 and Comparative Examples 4-5 were prepared into standard dumbbell-shaped specimens of type 1A in the national standard, and tested using a WDW universal testing machine with a tensile rate of 50 mm / min. The test results are shown in Table 3.
[0087] Notched impact strength test: The modified polyethylene samples prepared in Examples 15-27 and Comparative Examples 4-5 were prepared into strips with perpendicular surfaces and no defects on the edges using a ZHY-W universal prototyping machine. Then, a QYJ1251 notched prototyping machine was used to process an A-type notch with a notch angle of 45°±1°. The cantilever beam notched impact strength of the samples was measured using an XJJD-5J electronic impact testing machine in accordance with the national standard GB / T1843-2008, in kJ / m2. The test results are shown in Table 3.
[0088] Table 3 Test results of Examples 15-27 and Comparative Examples 4-5
[0089]
[0090]
[0091] From the results in Table 3, it can be seen that the tensile strength of Comparative Example 4 is slightly increased relative to that of Comparative Example 5. Since the glass fiber is not modified, there are a large number of polar groups on the surface of the glass fiber, which has poor bonding with the polyethylene material. The tensile strength of the glass fiber itself is very high, so the tensile strength of the composite material does not increase much; while the notched impact strength is relatively reduced. Since the glass fiber is an inorganic filler, it will play a role of heterogeneous nucleation when the high-density polyethylene crystallizes. The number of crystal nuclei increases, the grains become smaller, the crystallinity increases, the rigidity of the material is greatly improved, and the material deformation is poor. In addition, with the addition of glass fiber, the interface strength between the high-density polyethylene and the glass fiber is relatively The material is poor, when the material is subjected to impact force, the crack cannot expand on the surface of polyethylene and glass fiber, the spline cannot fully absorb energy, and the notched impact strength will decrease; from the results of Examples 15-18, it can be seen that due to the use of methacryloxypropyltrimethoxysilane, siloxane is hydrolyzed into silanol under acidic conditions, and covalently bonded to the hydroxyl group on the surface of glass fiber, and the free olefin group increases the compatibility of glass fiber and high-density polyethylene, thereby improving the mechanical properties of the material; from the results of Examples 15 and 19-24, it can be seen that with the increase in the amount of modified glass fiber, the tensile strength of the material gradually increases, but when subjected to external force, the matrix material transmits the force to the substrate. The tensile strength of the glass fiber itself is relatively large and its deformation is relatively small, so the tensile strength will be improved. The glass fiber plays a role in enhancing the load-bearing capacity in the composite material. In addition, the high-density polyethylene reacts with the free olefin bonds in the modified glass fiber, which reduces the surface energy of the fiber, improves the bonding ability of the high-density polyethylene and the glass fiber, and improves the tensile strength. However, with the increase in the amount of modified glass fiber, the notched impact strength decreases slowly. Due to the weak interfacial bonding strength between the matrix and the glass fiber, the cracks caused by the fiber breakage can change direction and expand along the interface, and the absorption capacity of the impact energy is improved. However, due to the high brittleness of the glass fiber, , which reduces the notched impact strength; it can be seen from the results of Examples 15 and 25-27 that with the increase in the amount of silane coupling agent, the notched impact strength and tensile strength of the material show a trend of first increasing and then decreasing. The main reason is that the introduction of olefin bonds increases the compatibility of glass fiber and high-density polyethylene and improves the bonding ability between materials. However, when too much silane coupling agent is added, it is in an oversaturated state, and the excess coupling agent has a negative impact on the material; from the results of Table 3, the tensile strength of the modified polyethylene obtained by adding KH-570 modified glass fiber is 52MPa, and the notched impact strength is 10.4KJ / m 2 , with significantly improved mechanical properties, the resulting high-density plastic barrel has good mechanical properties.
[0092] Embodiment 29
[0093] Preparation of benzoxazine derivatives:
[0094] 3 mol of aniline, 3.0 mol of 1,2-diphenyl-1,2-di(4-hydroxyphenyl)ethylene (phenolic hydroxyl group), and 6 mol of polyformaldehyde are stirred and mixed in a beaker at room temperature to obtain a mixed solution; 1 / 10 of the mixed solution is added to a 1000 ml flask, the temperature is raised to 70° C., and the reaction is carried out for 10 minutes to obtain a reaction solution 1; 1 / 10 of the second batch of the mixed solution is added to the reaction solution 1, and the reaction is carried out for 10 minutes to obtain a reaction solution 2; the remaining mixed solutions are added in sequence, and after the raw materials are added, the reaction temperature is maintained at 110° C., and the reaction is carried out under reflux for 20 minutes to obtain a reaction system; the reaction system is heated to 130° C., stirred and refluxed for 30 minutes to evaporate water, centrifuged, and vacuum dried at 80° C. for 2 hours to obtain a benzoxazine derivative.
[0095] The preparation of modified polyethylene refers to the preparation method and parameter conditions of Example 17.
[0096] Examples 30-43 refer to the preparation method and parameter conditions of Example 29, and the differences are shown in Table 4.
[0097] Comparative Example 6 refers to the preparation method and parameter conditions of Example 29, except that no benzoxazine flame retardant is added.
[0098] Comparative Example 7 refers to the preparation method and parameter conditions of Example 29, except that triphenyl phosphate is not added.
[0099] Example 44 Flame retardant performance test
[0100] The modified polyethylene prepared in Examples 29-43 and Comparative Examples 6-7 was sampled, and the sample size was 150 mm×6.5 mm×3 mm. Referring to GB / T 2406.2-2009, an oxygen index tester (model JF-3, Nanjing Jiangning District Analytical Instrument Factory) was used to perform limiting oxygen index detection. The test results are shown in Table 4.
[0101] Table 4 Flame retardant performance test of samples of Examples 29-43 and Comparative Examples 6-7
[0102]
[0103]
[0104] The results in Table 4 show that the limiting oxygen index of the polyethylene obtained by using a single flame retardant in Comparative Examples 6 and 7 is significantly lower than that of Examples 29-43. When BOZ is added alone, the heat resistance of the modified polyethylene can be increased, but the crosslinking density is low and the ideal flame retardant effect cannot be achieved. Since high-density polyethylene has a low limiting oxygen index and is difficult to form carbon itself, when DMMAP is added alone, it is difficult to form a carbon layer due to the lack of a carbon source, which plays a role in stopping combustion. At the same time, the organophosphorus flame retardant is easy to volatilize at low temperatures, further affecting the flame retardant effect. Comparative Examples 29-35 The results show that the use of organic phosphorus flame retardants in combination with other flame retardants can effectively improve the flame retardant properties of modified polyethylene. Since the polymetaphosphoric acid generated by the organic phosphorus flame retardant under combustion conditions is a glassy melt, it can form a protective film on the surface of the flame retardant material to isolate oxygen. At the same time, the phosphoric acid and polymetaphosphoric acid generated are strong acids with strong dehydration properties, which can dehydrate and carbonize the polymer and form a carbon layer on the polymer surface to isolate oxygen and prevent combustion. In addition, the PO· free radicals generated by the organic phosphorus flame retardant when heated can absorb a large amount of HO· and H· free radicals. The combustion reaction can be interrupted by the base. By comparing the results of Example 29 and Examples 36-39, it can be seen that with the increase in the amount of BOZ, the limiting oxygen index shows a trend of first increasing and then decreasing. Due to the good carbonization property of BOZ, it can participate in the carbonization flame retardant mode with the organic phosphorus flame retardant. During the ring-opening curing, BOZ forms a cross-linked network to inhibit the volatilization of DMMAP. At the same time, the phenolic hydroxyl groups formed during the ring-opening curing process react with the phosphoric acid and polymetaphosphoric acid generated by the decomposition of DMMAP at high temperature to increase the cross-linking density of the benzoxazine resin, and form a dense carbon layer on the surface of the combustion product. And achieve a better flame retardant effect; by comparing the results of Example 29 and Examples 40-43, it can be seen that with the increase of the total number of flame retardants, the flame retardant properties of the modified polyethylene gradually increase, however, excessive BOZ leads to reduced compatibility with the system, thereby reducing the mechanical properties of the modified polyethylene and affecting the comprehensive performance of the high-purity high-density polyethylene plastic barrel; from the results of Table 4, it can be obtained that by using BOZ / DMMAP as a flame retardant compound and controlling the amount of flame retardant and the component ratio, the limited oxygen index of the modified polyethylene obtained is 35%, which has significantly improved flame retardant properties.
[0105] Examples 45-55
[0106] The high-purity high-density polyethylene plastic barrel includes high-purity high-density polyethylene and modified polyethylene;
[0107] In a 10,000-class clean environment, 100 parts of branched high-density polyethylene, 5 parts of maleic anhydride grafted ethylene-octene copolymer, 15 parts of flame retardant, 20 parts of modified glass fiber, and 2 parts of antioxidant 1010 are poured into the corresponding raw material storage tank and stirred evenly to obtain a mixture 1; the high-purity high-density polyethylene is poured into the corresponding raw material storage tank and stirred and mixed evenly to obtain a mixture 2; the mixture 1 and the mixture 2 are vacuum dried at 100°C for 2h to obtain a dry material; the dry materials are respectively passed into two different screw extruders of a blow molding machine, the temperature of the screw extruder 1 is set to 160-200°C, and the temperature of the screw extruder 2 is set to 120-160°C, and the melt-modified polyethylene and the melt-high-purity high-density polyethylene are completely melted;
[0108] In a 10,000-class clean environment, 60 parts of the molten modified polyethylene and 40 parts of the molten high-purity high-density polyethylene are added to a mold with the barrel mouth facing downward, and the blow molding machine blows in a flow rate of 20-50m 3 / h of high-purity nitrogen gas for blow molding, and continue blowing for 20 minutes to obtain a plastic barrel; the plastic is introduced into the outside of the mold at a flow rate of 5-15m 3 / h of cooling water for cooling and solidification for 10 minutes to obtain a high-purity high-density polyethylene plastic barrel.
[0109] The specific parameters of Examples 45-55 are shown in Table 5.
[0110] Comparative Example 8 refers to the preparation method and parameter conditions of Example 45, except that air blow molding is used.
[0111] Comparative Example 9 refers to the preparation method and parameter conditions of Example 45, except that conventional high-density polyethylene is used instead of high-purity high-density polyethylene.
[0112] Example 56 Microparticle Determination
[0113] The impurity particle dissolution amount (number / ml) of the high-purity high-density polyethylene plastic barrels produced in Examples 45-55 and Comparative Examples 8-9 at 0d and 30d was tested using a particle analyzer (Liquid Sampler LS-60, Lighthouse, USA). The impurity particle (particle) determination method is as follows:
[0114] In a Class 100 clean environment, fill a molded plastic barrel with ultrapure water, and stand it upright for 20 minutes at 25°C just after extraction and after storage for 30 days before extraction. Take the test sample from the container as the test specimen. Clean the microparticle counter with ultrapure water before measurement; after cleaning, inject 10 ml of ultrapure water into the microparticle counter to measure the number of particles A (pieces / mL) in the ultrapure water; use 25 ml of the test specimen to clean the test device twice, and after cleaning, take out 10 ml of the ultrapure water of the test specimen from Examples 45-55 and Comparative Examples 8-9, inject it into the microparticle counter, and measure the number of particles B (pieces / mL) in the pure water in the container. Calculate the particle value P in 1 ml from the measured value: P = (BA) / 10; the test results of the total amount of 0d and 30d impurity particles are shown in Table 5; the changes in the dissolution amount of 0d and 30d particles of impurities with different particle sizes in Example 46 are shown in Figure 1 As shown; Comparative Example 8 The dissolution amount of impurities of different particle sizes 0d, 30d particles changes as shown Figure 2 shown.
[0115] Table 5 Dissolution amount of impurity particles in Examples 45-55 and Comparative Examples 8-9
[0116]
[0117]
[0118] Depend on Figure 1 , Figure 2 The results of Table 5 and the results of Comparative Examples 8-9 show that the amount of impurity particles dissolved from the high-density polyethylene plastic barrels prepared by using air as the blowing gas or using high-density polyethylene is significantly improved compared with Examples 45-55. The impurity particles increase under long-term storage conditions, affecting the performance of the plastic barrels. The results of Comparative Examples 45-50 show that the initial impurity particle dissolution amount of the plastic barrels prepared by using different screw extruder temperatures is low. Due to the use of high-temperature melting, nitrogen blowing reduces the impurity content of high-purity high-density polyethylene and modified polyethylene, and the impurity particles are reduced. However, as time goes on, the polyethylene material under the melting condition of lowering the temperature increases. Due to insufficient melting of the material, the molecules between the materials are not uniform. The introduction of bubbles during the blow molding process causes pores in the material. The adsorption capacity of the material to impurities increases under long-term storage conditions, and the amount of impurity particles dissolved increases. By comparing the results of Example 45 and Examples 51-53, it can be seen that the size of the nitrogen flow rate has little effect on the amount of impurity particles dissolved. The results of Examples 45 and Examples 54-55 show that the cooling water flow rate is too large, the plastic barrel is cooled rapidly, and a large amount of bubbles are released. The bubbles are formed between the molecules of the plastic barrel and filled in the pores. Long-term storage increases the content of impurity particles and affects the overall performance. The cooling water flow rate is too low, and the cooling and curing time is prolonged. Comprehensive Table 5, Figure 1-2The results show that the high-density polyethylene plastic barrels prepared by nitrogen blow molding, and the screw temperature, nitrogen flow rate and cooling water flow rate are controlled. The 0d impurity particle dissolution amount of the prepared high-density polyethylene plastic barrels is 8 pieces / ml; the 30d impurity particle dissolution amount is 15 pieces / ml, showing a significantly reduced impurity particle dissolution amount.
[0119] Examples 57-64
[0120] The plastic barrel prepared in Example 46 is cleaned and sanded to a rough surface to prepare a rough-surface plastic barrel; the rough-surface plastic barrel is coated with epoxy resin adhesive and pasted with glass fiber cloth to obtain a fiber-treated plastic barrel; the fiber-treated plastic barrel is placed in a mold for hot pressing and curing at a curing temperature of 90-120°C, a curing time of 30-90min, and a curing pressure of 40-60MPa to obtain a cured plastic barrel; the cured plastic barrel is demolded and cooled at room temperature to obtain a high-density polyethylene plastic barrel.
[0121] The specific parameters are shown in Table 6.
[0122] Comparative Example 10 refers to the preparation method and parameter conditions of Example 57, except that glass fiber cloth is not added for curing.
[0123] Example 65 Drop resistance test
[0124] The plastic barrels produced in Examples 57-64 and Comparative Example 10 were subjected to a drop resistance test. The volume of the plastic barrels was 100 L. The drop test was performed at a temperature of 23°C ± 2°C and a relative humidity of 50% ± 2%. The steps are as follows:
[0125] The content of the plastic barrel is clean water, the amount of clean water injected is 100L of the plastic barrel capacity, and the drop height is 1.5m. The drop test is divided into angle drop and straight line drop. In the angle drop, the center line of the plastic barrel is at an angle of 10 with the vertical line, and it falls freely to the cement floor. After falling once, the damage of the test plastic barrel is checked; in the straight line drop, the bottom of the plastic barrel falls vertically to the cement floor. After falling once, the damage of the test plastic barrel is checked. The test results are shown in Table 6.
[0126] Table 6 Anti-drop performance test of Examples 57-64 and Comparative Example 10
[0127]
[0128] The results in Table 6 show that in Comparative Example 10, no glass fiber cloth is used to entangle the outside of the barrel to form a stable glass fiber anti-fall layer. The barrel body will crack and leak when the plastic barrel falls from an angle or falls in a straight line. The results in Examples 57-59 show that when the curing temperature is high, the barrel body will have cracks when the plastic barrel falls in a straight line. Due to the addition of epoxy resin adhesive, a cross-linking reaction can occur with the high-density polyethylene plastic barrel during the curing process, so that a stable covalent bonding effect is formed between the glass fiber cloth and the plastic barrel. As the temperature increases, the cross-linking effect becomes stronger, the force offset is weakened, and the plastic barrel material becomes brittle and easily cracked. Comparative Example 57 and Example From the results of Example 60-62, it can be seen that a too short curing time is not conducive to the cross-linking between the glass fiber cloth and the plastic barrel, thereby reducing the drop resistance of the plastic barrel. If the curing time is too long, the cross-linking points increase, the brittleness increases, and it is easy to break. From the results of Example 57 and Example 63-64, it can be seen that the change of curing pressure has little effect on the drop resistance, and the change of pressure does not affect the generation of cross-linking points. From the results of Table 6, it can be seen that by wrapping glass fiber cloth around the surface of the plastic barrel and controlling the curing time and curing temperature, the high-density polyethylene plastic barrel prepared in the 1.5m drop test showed that the barrel body had no cracks or leakage in both straight-line drop and corner drop, showing significantly improved drop resistance.
[0129] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production process for high-purity high-density polyethylene plastic barrels, characterized by: The plastic barrel includes high-purity high-density polyethylene, modified polyethylene, and glass fiber cloth; The modified polyethylene comprises 80-120 parts of branched high-density polyethylene, 10-25 parts of modified glass fiber, 5-25 parts of flame retardant, 5 parts of compatibilizer, and 2 parts of antioxidant; The branched high-density polyethylene is prepared by melt extrusion of 5-25 parts of lauroyl peroxide, high-density polyethylene, and 10-40 parts of monomer olefin; The production process of the plastic barrel comprises the following steps: In a clean environment, the modified polyethylene is added to a modified polyethylene raw material storage tank, and stirred evenly to obtain a mixed material 1; the high-purity high-density polyethylene is added to a high-purity polyethylene raw material storage tank and stirred evenly to obtain a mixed material 2; the mixed material 1 and the mixed material 2 are respectively introduced into a screw extruder 1 and a screw extruder 2, and are completely melted to obtain molten modified polyethylene and molten high-purity high-density polyethylene; In a clean environment, 60 parts of the molten modified polyethylene and 40 parts of the molten high-purity high-density polyethylene are added into a mold with the barrel mouth facing downward, and the blow molding machine blows in a flow rate of 20-50m 3 / h of high-purity nitrogen for blow molding, and continuously blow to obtain a plastic barrel; the plastic barrel is passed through the outside of the mold with a flow rate of 5-15m 3 / h of cooling water to cool and solidify to obtain a polyethylene plastic barrel; The polyethylene plastic barrel is cleaned and polished to obtain a rough surface plastic barrel; glass fiber cloth is pasted on the rough surface plastic barrel to obtain a fiber-treated plastic barrel; the fiber-treated plastic barrel is placed in a mold for hot pressing and curing, demolding, and cooling at room temperature to obtain a high-purity and high-density polyethylene plastic barrel.
2. The production process of a high-purity high-density polyethylene plastic barrel according to claim 1, characterized in that: The monomer olefin is selected from one of 1-propylene, 1-butene, 1-pentene and 1-hexene.
3. The production process of a high-purity high-density polyethylene plastic barrel according to claim 1, characterized in that: The method for preparing branched high-density polyethylene comprises the following steps: The lauroyl peroxide, the high-density polyethylene, and the monomer olefin compound are placed in a vacuum drying oven and dried at 60° C. for 2 hours to obtain a dry material; the dry material is added to a high-speed mixer and stirred at 200 r / min for 30 minutes to obtain a mixed material; the mixed material is added to a twin-screw extruder, subjected to a melt reaction process at a temperature range of 160° C.-200° C., a main engine speed of 80 r / min, and reacted for 2 hours to obtain a reactant; the reactant is crushed by a crusher to obtain the branched high-density polyethylene.
4. The production process of a high-purity high-density polyethylene plastic barrel according to claim 1, characterized in that: The preparation of the modified glass fiber comprises the following steps: The glass fiber is added into a muffle furnace, and burned at 350° C. for 10 minutes to remove the paraffin on the surface to obtain the fired glass fiber; the fired glass fiber is added into a 10% HCl solution for immersion for 2 hours, and vacuum dried at 100° C. for 1 hour to obtain the acidic glass fiber; the silane coupling agent is dissolved in a solution of anhydrous ethanol and deionized water in a volume ratio of 1:1, and mixed at 200 rpm to obtain a mixed solution; the acidic glass fiber is added into the mixed solution, ultrasonicated for 2 hours, taken out, and dried at 100° C. to obtain the modified glass fiber.
5. The production process of a high-purity high-density polyethylene plastic barrel according to claim 4, characterized in that: The silane coupling agent is selected from one of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and methacryloxypropyltrimethoxysilane; and the amount of the silane coupling agent is 1-8 parts.
6. The production process of a high-purity high-density polyethylene plastic barrel according to claim 1, characterized in that: The flame retardant includes flame retardant 1 and flame retardant 2; the flame retardant 1 is selected from one of benzoxazine derivatives, polyvinyl chloride, polyphenylene ether, and phenolic resin; the flame retardant 2 is selected from one of triphenyl phosphate, tricresyl phosphate, phenyl aluminum phosphinate, and dimethyl methylphosphonate; the component dosage ratio of the flame retardant 1 to the flame retardant 2 is 1-4:1-4.
7. The production process of a high-purity high-density polyethylene plastic barrel according to claim 1, characterized in that: The temperature of the screw extruder 1 is 160-200°C, and the temperature of the screw extruder 2 is 120-160°C.
8. The production process of a high-purity high-density polyethylene plastic barrel according to claim 1, characterized in that: The curing temperature of the hot pressing curing is 90-120° C., the curing time is 30-90 min, and the curing pressure is 40-60 MPa.
9. The production process of a high-purity high-density polyethylene plastic barrel according to claim 1, characterized in that: The compatibilizer is selected from maleic anhydride grafted ethylene-octene copolymer; and the antioxidant is selected from antioxidant 1010.
10. A high-purity high-density polyethylene plastic barrel, characterized by: The high-purity high-density polyethylene plastic barrel comprises the high-purity high-density polyethylene, the modified polyethylene, and the glass fiber cloth; the high-purity high-density polyethylene plastic barrel is prepared by the production process described in any one of claims 1 to 9; the environmental stress cracking time of the modified polyethylene in the plastic barrel is 1356h; the tensile strength of the modified polyethylene in the plastic barrel is 52MPa, and the notched impact strength is 10.4KJ / m 2 ; The limiting oxygen index of the modified polyethylene in the plastic barrel is 35%; the 0d impurity particle dissolution amount of the high-density polyethylene plastic barrel is 8 pieces / ml; the 30d impurity particle dissolution amount is 15 pieces / ml; in the 1.5m drop test of the high-density polyethylene plastic barrel, there is no cracking or leakage in the barrel body when falling in a straight line or at an angle.
Citation Information
Patent Citations
High-density polyethylene resin composition for floating photovoltaic tanks and its preparation method
CN112679835B
A heat-resistant biodegradable plastic and its preparation method
CN114106421B
Benzoxazine-containing high-gloss halogen-free flame-retardant plastic and application thereof
CN102167882A
Heat-resistant and pressure-resistant polyethylene composite pipe
CN102705591A
Long-chain branched high-density polyethylene material resisting environmental stress cracking and preparation method thereof
CN105924584A